2009
DOI: 10.1128/jb.01160-09
|View full text |Cite
|
Sign up to set email alerts
|

AlipA(yutB) Mutant, Encoding Lipoic Acid Synthase, Provides Insight into the Interplay between Branched-Chain and Unsaturated Fatty Acid Biosynthesis inBacillus subtilis

Abstract: Lipoic acid is an essential cofactor required for the function of key metabolic pathways in most organisms. We report the characterization of a Bacillus subtilis mutant obtained by disruption of the lipA (yutB) gene, which encodes lipoyl synthase (LipA), the enzyme that catalyzes the final step in the de novo biosynthesis of this cofactor. The function of lipA was inferred from the results of genetic and physiological experiments, and this study investigated its role in B. subtilis fatty acid metabolism. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 56 publications
(38 reference statements)
5
41
0
Order By: Relevance
“…Although LipA Ct shows a fairly high degree of homology to the E. coli LipA and has all of the canonical residues that are typical for this enzyme family, it failed to restore growth of an E. coli mutant lacking lipA. Homologs of LipA from other organisms have been shown to complement a similar E. coli lipA mutant, suggesting that heterologous enzymes are capable of functioning in vivo and complementing an E. coli mutant (26,44). Bacillus subtilis possesses two ligases and a lipoic acid synthase but no putative lipB, an arrangement similar to that encountered in chlamydiae (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although LipA Ct shows a fairly high degree of homology to the E. coli LipA and has all of the canonical residues that are typical for this enzyme family, it failed to restore growth of an E. coli mutant lacking lipA. Homologs of LipA from other organisms have been shown to complement a similar E. coli lipA mutant, suggesting that heterologous enzymes are capable of functioning in vivo and complementing an E. coli mutant (26,44). Bacillus subtilis possesses two ligases and a lipoic acid synthase but no putative lipB, an arrangement similar to that encountered in chlamydiae (26).…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus subtilis possesses two ligases and a lipoic acid synthase but no putative lipB, an arrangement similar to that encountered in chlamydiae (26). The B. subtilis lipA is essential for growth of the bacteria in minimal medium without exogenous lipoic acid, suggesting that it is capable of de novo lipoic acid biosynthesis, even in the absence of a putative LipB transferase (26). The existence of a similar pathway in chlamydiae cannot be ruled out since we have shown that LplA1 Ct expressed in ATM967 (⌬lplA ⌬lipB::kan) can lipoylate target proteins even in the absence of exogenous lipoic acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of these more complex lipoyl synthesis pathways was found in Bacillus subtilis, a Gram-positive bacterium that is evolutionarily far removed from the Gram-negative E. coli. B. subtilis encodes a LipA that could functionally replace E. coli LipA, and disruption of the gene resulted in lipoate (or the products of the 2-oxoacid dehydrogenases) being required for growth (117). Although lipoate supplementation should require lipoate ligase activity, it was unclear why this bacterium encoded three putative lipoate ligases and no homologue of the LipB octanoyltransferase (87).…”
Section: Involvement Of the Glycine Cleavage H Protein In 2-oxoacid Dmentioning
confidence: 99%
“…1A). BCFAs serve as the principal fatty acids in B. subtilis membranes under standard growth conditions and also tailor membrane integrity by altering ratios of BCFAs in response to thermal perturbation, a multifaceted process known as homeoviscous adaptation (1,14,38,44,50). To synthesize BCFAs, BCKAs are converted first to their acyl-coenzyme A (acyl-CoA) derivatives and then to their carboxylic acid derivatives by functions encoded by the bkd operon (13,20).…”
mentioning
confidence: 99%